2019
DOI: 10.1097/htr.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antidepressants on Depression After Traumatic Brain Injury: A Meta-analysis

Abstract: This meta-analysis found no significant benefit of antidepressant over placebo in the treatment of MDD following TBI. Pooled estimates showed a high degree of bias and heterogeneity. Prospective studies on the impact of antidepressants in well-defined cohorts of TBI patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 57 publications
0
27
2
Order By: Relevance
“…Depression is a common post-TBI disturbance that is often treated with neuroactive medication. Post-TBI depression is generally managed with selective serotonin reuptake inhibitors (SSRIs), despite only minimal evidence of their efficacy in TBI (Yue et al, 2017; Kreitzer et al, 2018). It is suggested that there may be a causative relationship between depression and dysfunctional adult neurogenesis, with antidepressant medications exhibiting their effects via increases in neurogenesis (Santarelli et al, 2003; Eisch and Petrik, 2012; Yun et al, 2016).…”
Section: The Effect Of Tbi Interventionsmentioning
confidence: 99%
“…Depression is a common post-TBI disturbance that is often treated with neuroactive medication. Post-TBI depression is generally managed with selective serotonin reuptake inhibitors (SSRIs), despite only minimal evidence of their efficacy in TBI (Yue et al, 2017; Kreitzer et al, 2018). It is suggested that there may be a causative relationship between depression and dysfunctional adult neurogenesis, with antidepressant medications exhibiting their effects via increases in neurogenesis (Santarelli et al, 2003; Eisch and Petrik, 2012; Yun et al, 2016).…”
Section: The Effect Of Tbi Interventionsmentioning
confidence: 99%
“…This was consistent with the results of previous pair-wise meta-analyses, which addressed the benefits of pharmacologic treatments for post-TBI depressive symptoms. [10][11][12] In addition, based on the frequentist model of network meta-analysis and the SUCRA method, the present network meta-analysis provided further evidence to support the superiority of individual pharmacologic treatments. Specifically, our findings demonstrated that methylphenidate was associated with the best improvement of all pharmacologic treatments.…”
Section: Discussionmentioning
confidence: 70%
“… 9 In spite of the lack of specific pharmacologic guidelines for the treatment of post-TBI depression, several pair-wise meta-analyses have investigated the efficacy of antidepressants, with mixed results. 10 12 On the other hand, nonpharmacologic treatments encompass psychotherapeutic approaches such as supportive psychotherapy, cognitive behavioural therapy (CBT) and mindfulness-based CBT. 13 Surprisingly, despite the prevalence and severity of post-TBI depression, there is no consensus on standard therapeutic guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) are currently the first-line recommended treatment for depression in patients recovering from concussion [4]. However, despite their widespread use for treating depression in patients with and without neurologic conditions, a recent meta-analysis suggested that SSRIs were actually no more effective at reducing depressive symptoms in mTBI patients than placebo [5]. While caution is warranted in prematurely abandoning the use of SSRIs for this population, given that the benefits may still outweigh potential risks [4], these negative findings should motivate researchers to expand their horizons to identify additional therapeutic options for treating depression following concussion.…”
Section: Concussion and Depressionmentioning
confidence: 99%